2014
DOI: 10.1186/1472-6831-14-45
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a questionnaire for self-assessment of complete dentures

Abstract: BackgroundDemand for complete denture treatment is expected to rise over several decades. However, to date, no questionnaire on complete dentures, as evaluated by edentulous patients, has been shown to be reliable and valid. This study sought to assess the reliability and validity of Patient’s Denture Assessment (PDA), which provides a multidimensional evaluation of dentures among edentulous patients.MethodsPatients, who had new complete dentures fabricated at the University Hospital of Dentistry, Tokyo Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 22 publications
5
59
1
3
Order By: Relevance
“…Moreover, the high level of association between methods suggested that participants tended to provide similar responses on both application sessions. For denture satisfaction, correlation levels were slightly lower than those found in a study on Japanese patients 20. This can be explained by the different levels of education for the two study samples.…”
Section: Discussioncontrasting
confidence: 79%
“…Moreover, the high level of association between methods suggested that participants tended to provide similar responses on both application sessions. For denture satisfaction, correlation levels were slightly lower than those found in a study on Japanese patients 20. This can be explained by the different levels of education for the two study samples.…”
Section: Discussioncontrasting
confidence: 79%
“…Patients make a self-assessment of their dentures using the Patient’s Denture Assessment (PDA) [33]. The PDA comprises 22 items covering six subscales classified as function, lower denture, upper denture, expectation, aesthetics and speech, and importance.…”
Section: Methodsmentioning
confidence: 99%
“…When the MIIC of scale is greater than 0.3, the internal consistency of scale is usually acceptable [26]. The mean inter-item correlation coefficient values of the whole BARSHSS-CV and all factors were greater than 0.5.…”
Section: Discussionmentioning
confidence: 99%